Lactic Acid Fermentation of Peppers - Alberto, Maria Rosa (2013)
Different peppers fermentations (Capsicum annum, grossum variety) were assayed: spontaneous, native microflora sup- plemented individually with Lactobacillus plantarum N8, Leuconostoc mesentereroides L. or Pediococcus pentosaceus 12p and by pure or combined cultures of these lactic acid bacteria (LAB). In order to eliminate the native flora, different kinds of heat treatment were assayed. The treatment selected was heating in autoclaved after research 3/4 atmosphere and to turn off. Fermentations were carried out at 22°C and 30°C and the culture media contained 2% or 0.2% glucose and 4% NaCl. Sugar consumption, pH reduction and acid production were higher at 30°C than at 22°C. At both tem- peratures, spontaneous fermentation showed a slower rate reduction in pH than inoculated samples. Diminution in pH in presence of 2% glucose was faster than at 0.2%, but minimum pH was in both case lower than 3.0. Maximum growth was reached between 2 and 5 days of fermentation in all the samples assayed. After 30 days of incubation in presence of 2% glucose the survival of LAB was nearly 5 log ufc/ml. The survival was higher at the lower temperature assayed for both glucose concentrations. Organoleptic properties of peppers fermented with a mixed culture of Leuconostoc mes- enteroides and Pediococcus pentosaceus were found best by a human panel. This sample has a relation lactic acid/acetic acid of nearly 3 in the conditions assayed.